2018
DOI: 10.1371/journal.pone.0208550
|View full text |Cite
|
Sign up to set email alerts
|

Gas6 is dispensable for pubertal mammary gland development

Abstract: Mammary gland development is a complex and dynamic process that occurs mainly postnatally. Ductal elongation and branching morphogenesis are regulated by a plethora of factors, including cytokines, hormones, growth factors and the extracellular matrix. Gas6 is a secreted gamma-carboxylated protein that binds to a family of receptors tyrosine kinase receptors known as the TAMR family (Tyro3, Axl, Mer). Gas6 function in developmental processes has been shown in nervous, reproductive and immune systems. In this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 35 publications
2
8
0
Order By: Relevance
“…Here, we showed that Gas6 is highly expressed in the ductal epithelial cells of normal breast with faint stromal expression ( Fig. 1), which is consistent with our previous studies of the normal murine mammary gland 19 . Epithelial-derived Gas6 protein expression was significantly increased in DCIS, but declined in invasive tumors (Fig.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Here, we showed that Gas6 is highly expressed in the ductal epithelial cells of normal breast with faint stromal expression ( Fig. 1), which is consistent with our previous studies of the normal murine mammary gland 19 . Epithelial-derived Gas6 protein expression was significantly increased in DCIS, but declined in invasive tumors (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…1a). In support of our previous studies in the mouse mammary gland 19 , Gas6 was highly expressed in the ductal epithelium of normal breast (adjacent normal). Compared to normal tissue, there was a significant increase in Gas6 protein in pure DCIS.…”
Section: Gas6 Expression Declines In Invasive Breast Tumorssupporting
confidence: 89%
“…A conundrum raised by our results is that Axl-null animals are able to develop functional mammary glands, yet upon ex vivo transplantation into cleared fat pads of recipient mice the sorted Axl-null epithelial cells showed a significant reduction in the ability to reconstitute the mammary tree. Relatedly, the GAS6-null mouse also develops functional mammary glands ( Mills et al., 2018 ). Knockout of the TAM family member Mer did show a developmental phenotype during post-lactational involution as it was shown necessary for mediating epithelial efferocytosis of apoptotic cells, but AXL and Tyro3 were explicitly not required for that process ( Sandahl et al., 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to neoplastic cells, Gas6 is expressed by luminal progenitor and basal cells around the ductal lining of the mammary tissue [ 65 ]. In the bone microenvironment, Gas6 is secreted by osteoblasts that are involved in forming bones [ 66 , 67 , 68 ].…”
Section: Gas6 and Axl Expression In The Tumor Microenvironmentmentioning
confidence: 99%